Innovative use of fly ash-finely powdered glass cullet as a nano additives for a sustainable concrete: Strength and microstructure and cost analysis. (December 2022) - Amran, Mugahed; Onaizi, Ali M.; Qader, Diyar N.; Murali, G.
Abstract: As the global population and industrial and commercial activities continue to expand, the accompanying amount of industrial and solid waste increases constantly. The subject of utilizing and recycling solid wastes as building materials has recently drawn considerable interest from researchers from all over the world. The amount of waste glass produced each year has grown rapidly in the past several decades, and as a great source of active silica, finely powdered glass cullet (FPGC) is an alluring pozzolanic additive, making it a pozzolanic ingredient that can be included in concrete mixtures. These recycling initiatives for FPGC have the potential to reduce solid waste, greenhouse gas emissions, and raw waste of materials while providing sustainable benefits and offering an effective solution for a significant environmental challenge that necessitates the pursuit of radical solutions. This study aimed to investigate the properties and microstructure of high-proportion fly ash-based green concrete composite improved with FPGC and evaluate its environmental sustainability performance. A total of six mixtures containing 50 % fly ash as cement replacement and 0 %, 2 %, 4 %, 6 %, 8 %, and 10 % FPGC were developed. The limitation of this study is to examine the strength properties as well as to conduct a cost analysis. The workability, compressive strength, flexural strength, modulus of elasticity, and water absorption were tested. In addition, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD) and Thermogravimetric analysis (TGA) were used to monitor the microstructural properties. Total energy consumption, total CO2 emission, and total costs were computed to determine the life cycle of the developed binders. Results revealed that workability slightly decreased with the increase in FPGC contents, whereas the strength properties increased with the increment in FPGC content up to 6 %. However, when the FPGC content exceeded 6%, the strength properties gradually decreased. The optimum contents were recorded at 50 % fly ash and 6 % FPGC. The resulting denser and homogeneous microstructures showed a positive effect on the reduction of total energy consumption, total CO2 emissions, and production costs of the synthesized binders. Therefore, the use of FPGC will enable the production of green concrete with satisfactory engineering characteristics and contribute to the achievement of sustainability goals of United Nations through pollution reduction, waste recycling, and landfill concerns. In addition, it would be incredibly beneficial to any country's long-term growth since landfill waste disposal issues would be avoided and minimized. The major findings of this study are expected to lay the groundwork for future research and provide a better understanding of the behavior of multi-blend modified concrete made from waste in a cost-effective and environmentally friendly manner.